Comparative Study for String Matching Algorithms - Ammar Waysi AlTuhafi (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
String matching became important application nowadays, the increasing of database such as websites, document, DNA, etc., leads to the urgent needs for string matching; string matching has many applications such as DNA, protein matching, internet search engine, all these types of application of string matching, beside the huge amount of database lead to increase the need to fast and efficient string matching algorithms. This study is about comparing among most well-known string matching algorithms; it focuses on four types of string matching algorithms, each one of them working in a different way. The four are tested with four types of data; ASCII (256 character), English alphabet (26 characters), DNA (4 character), and protein (20 character), with different pattern length (100, 50, 20, 10, 5) results shown based on number of comparisons and time.